Isolation and Characterization of Dehalobacter sp. Strain TeCB1 Including Identification of TcbA: A Novel Tetra- and Trichlorobenzene Reductive Dehalogenase - Alfán-Guzmán, Ricardo; Ertan, Haluk; Manefield, Mike; Lee, Matthew (Frontiers in Microbiology, 2017)
Dehalobacter sp. strain TeCB1 was isolated from groundwater near Sydney, Australia that is polluted with a range of organochlorines. The isolated strain is able to grow by reductive dechlorination of 1,2,4,5-tetrachlorobenzene to 1,3- and 1,4-dichlorobenzene with 1,2,4-trichlorobenzene being the intermediate daughter product. Transient production of 1,2-dichlorobenzene was detected with subsequent conversion to monochlorobenzene. The dehalogenation capability of strain TeCB1 to respire 23 alternative organochlorines was examined and shown to be limited to the use of 1,2,4,5-tetrachlorobenzene and 1,2,4-trichlorobenzene. Growth on 1,2,4-trichlorobenzene resulted in the production of predominantly 1,3- and 1,4-dichlorobenzene. The inability of strain TeCB1 to grow on 1,2-dichlorobenzene indicated that the production of monochlorobenzene during growth on 1,2,4,5-tetarchlorobezene was cometabolic. The annotated genome of strain TeCB1 contained only one detectable 16S rRNA gene copy and genes for 23 full-length and one truncated Reductive Dehalogenase (RDase) homologs, five unique to strain TeCB1. Identification and functional characterization of the 1,2,4,5-tetrachlorobenzene and 1,2,4-trichlorobenzene RDase (TcbA) was achieved using native-PAGE coupled with liquid chromatography tandem mass spectrometry and. Interestingly, TcbA showed higher amino acid identity with tetrachloroethene reductases PceA (95% identity) from Dehalobacter restrictus PER-K23 and Desulfitobacterium hafniense Y51 than with the only other chlorinated benzene reductase (i.e. CbrA (30% identity)) functionally characterized to date.